(untitled) (Epidemiology, Biostatistics, and Public Health, 2022)
This short and essential book [1] is addressed essentially to medical and public health students, and to anyone interested in a summary up to date presentation of cancer epidemiology and prevention. It is subdivided into four major sections, that include principles of primary and secondary cancer prevention, the current global burden of neoplasms,...